The Role of Socioeconomic Status in Financial Socialization Practices of African American Women in the United States - Anita Johnson; Karina Kasztelnik (Financial Markets, Institutions and Risks)
This study delves into the influence of socioeconomic status on the financial socialization practices of African American women in the United States. Financial socialization, defined as the process by which individuals acquire financial knowledge, skills, and behaviors, is impacted by various factors, including family dynamics, cultural values, and socioeconomic conditions. However, there is a lack of research specifically focusing on how socioeconomic status affects the financial socialization practices among African American women, who have historically encountered unique economic challenges and systemic inequalities. Employing a qualitative approach, this research integrates the analysis of national survey data with qualitative interviews conducted with African American women from diverse socioeconomic backgrounds. The study explores how socioeconomic status impacts the ways these women educate their children about money management, savings, credit use, and overall financial responsibility. The findings highlight significant variations in financial socialization practices based on socioeconomic status, indicating that women from higher socioeconomic backgrounds tend to utilize more structured and proactive financial education strategies, while those from lower socioeconomic backgrounds often encounter barriers such as limited access to financial resources and education. Furthermore, the study reveals how African American women across all socioeconomic status levels employ culturally specific strategies to overcome systemic barriers and cultivate financial resilience in their families. The results underscore the importance of considering socioeconomic status in developing tailored financial literacy programs and policies that address the distinct needs and challenges faced by African American women. By offering a nuanced understanding of how socioeconomic status influences financial socialization, this research contributes to broader discussions on economic empowerment and financial inclusion within African American communities in the United States.